Rethinking the economics of war : the intersection of need, creed, and greed - Arnson, Cynthia; Arnson, Cynthia; Zartman, I. William (Washington, D.C. : Woodrow Wilson Center Press ; Baltimore : Johns Hopkins University Press, 2005)
This collection of essays questions the adequacy of explaining today's internal armed conflicts purely in terms of economic factors and re-establishes the importance of identity and grievances in creating and sustaining such wars. Countries studied include Lebanon, Angola, Colombia and Afghanistan.
Keywords: War -- Economic aspects -- Developing countries; Civil war -- Economic aspects -- Developing countries; Developing countries -- Economic conditions; Developing countries -- Politics and government